Psikoterapi Spiritual: Analisis Pendekatan Pengobatan Alter-natif Ustadz Dhanu dalam Penyembuhan Psikis - Edi Fatra; Wulan Novitasari; Aulia Ulfatun Khasanah (Fakultas Dakwah UIN KHAS Jember, 2025)
Nowadays, 56% of the factors that cause physical illness come from psychological factors, daily thoughts and actions. According to a scholar who understands alternative medicine, one of whom is Ustadz Dhanu, is of the opinion that all diseases arise because a person often indulges in lust, holds grudges, even harbors anger, so that Allah gives a warning to humans to return to the right path, namely being guided by the Al-Qur'an. an and the sunnah of the prophet. Ustadz Dhanu prioritizes a holistic approach in maintaining health by combining physical, mental and spiritual aspects. One of the treatments used is psychotherapy, a healing method using suggestion, psychology and moral improvement. Suggestion has an important role and benefits in stimulating good hormones in the body which will later release antibodies (good cells that fight disease).